The fifth beginning what six million years of human history can tell us about our future - Kelly, Robert L. (University of California Press, 2016)
"In The Fifth Beginning, archeologist Robert Kelly explains how the study of our cultural past can predict the future of humanity. In an eminently readable style, Kelly identifies four key pivot points in the six-million-year history of human development: the emergence of technology, culture, agriculture, and the state. In each example, the author examines the long-term processes that resulted in a definitive no-turning-back change for the organization of society. Kelly then looks ahead, giving us evidence for what he calls a fifth beginning, one that began about AD 1500. Some might call it 'globalization, ' but the author places it in its larger context: a 5,000-year arms race, capitalism's global reach, and the cultural effects of a worldwide communication network. Kelly predicts the emergent phenomena of this fifth beginning will include the end of war as a viable way to resolve disputes, the end of capitalism as we know it, the widespread appearance of world citizenship, and forms of cooperation that end nation-states' near-sacred status. It's the end of life, as we have known it. However, this book and the author are cautiously optimistic: it dwells not on the coming chaos, but on humanity's great potential"--Provided by publisher.